Education Administrators’ Perceived Political Influence On Curriculum Development in Tertiary Institutions of Bauchi State, Nigeria - Ibrahim, U.,; Edemenang,, C. E.,; Deba,, A. A.; Abba,, I. S. D. (Kashere Journal of Education, 2021)
The study explored Education Administrators’ Perceived Political Influence on Curriculum Development in Tertiary Institutions of Bauchi State, Nigeria. The study adopted qualitative research approach using case study design. Three specific objectives and three research questions were used to guide the study. The population consisted of senior administrators from all the state tertiary institutions in the three geo-political zones in Bauchi State. The study had sample of respondents drawn from the population using purposive sampling technique. The numbers that constituted the sample size were five and drawn from College of Education Azare, College for Legal and Islamic Studies Misau and College of Education Kangere within the three educational zones of Bauchi state. Area of the study is Bauchi state. Semi-structured interview, observation and document analysis were used for data collection. Data collected were analyzed using content and thematic analyses to answer the research questions of this study. The results of the study were discussed in details from interviews and triangulated with the findings made from observations and documents. Based on the findings, it was concluded that politics affects curriculum development positively. It was recommended among others that politics of curriculum development should be done bearing in mind rationale economic calculus for educational development of tertiary institutions. Politics of curriculum development should be intended to improved sustainable tertiary institutions development and not the other way round. In spite of these, the politics of curriculum development has made it difficult to properly plans and administer educational policies and management which has affected the enrolments, federal character policies, control of education among others